Association Between Post-procedure Cerebral Blood Flow Velocity and Severity of Brain Edema in Acute Ischemic Stroke With Early Endovascular Therapy - Pan, Jie; Wu, Huadong; Wu, Tingting; Geng, Yu; Yuan, Ruozhen (Frontiers in Neurology, 2022)
Objectives: We aimed to investigate the association between post-procedure cerebral blood flow velocity (CBFV) and severity of brain edema in patients with acute ischemic stroke (AIS) who received early endovascular therapy (EVT). Methods: We retrospectively included AIS patients who received EVT within 24 hours of onset between February 2016 and November 2021. Post-procedure CBFV of the middle cerebral artery was measured in the affected and the contralateral hemispheres using transcranial Doppler ultrasound. Severity of brain edema was measured using the three-level cerebral edema grading from the Safe Implementation of Thrombolysis in Stroke-Monitoring Study, with grades 2-3 indicating severe brain edema. Association between CBFV parameters and severity of brain edema was analyzed. Results: A total of 101 patients (mean age 64.2 years, 65.3% male) were included, of whom 56.3% (57/101) suffered brain edema [grade 1, 23 (22.8%); grade 2, 10 (9.9%); grade 3, 24 (23.8%)]. Compared to patients with non-severe brain edema, patients with severe brain edema had lower affected/contralateral ratios of systolic CBFV (median 1.0 vs. 1.2, P=0.020) and mean CBFV (median 0.9 vs. 1.3, P=0.029). Multivariate logistic regression showed that severe brain edema was independently associated with affected/contralateral ratios of systolic CBFV [odds ratio (OR)=0.289, 95% confidence interval (CI): 0.069-0.861, P=0.028] and mean CBFV (OR=0.278, 95% CI: 0.084-0.914, P=0.035) after adjusting for potential confounders. Conclusion: Post-procedure affected/contralateral ratio of CBFV may be a promising predictor of brain edema severity in patients with AIS who received early EVT.